2009
DOI: 10.4103/0971-5851.64253
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancers in a referral hospital in northern Nigeria

Abstract: Background:We undertook this study to determine the relative frequencies of childhood malignancies and their age – sex distribution in this environment.Materials and Methods:Hospital-based data of histological and cytologically confirmed cases of malignancies in children, aged ≤ 15 years, was collated over a period of 11 years, from the Cancer Registry.Results:A total of 329 children aged ≤ 15 years, with confirmed malignant disease, was recorded. This constituted 8.44% of all malignancies diagnosed in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 9 publications
7
17
0
1
Order By: Relevance
“…Burkitt lymphoma was the commonest in eight of the centres namely Enugu, Zaria, Jos, Ekiti, Calabar, Sagamu, Abia and Gwagwalada with prevalence ranging from 18.3 to 65.0% of malignant tumours of child hood in the various centers [9][10][11][18][19][20][21][22] . These centres are spread across the FCT and five geopolitical zones but excluding the north east geopolitical zone.…”
Section: Prevalencementioning
confidence: 99%
See 3 more Smart Citations
“…Burkitt lymphoma was the commonest in eight of the centres namely Enugu, Zaria, Jos, Ekiti, Calabar, Sagamu, Abia and Gwagwalada with prevalence ranging from 18.3 to 65.0% of malignant tumours of child hood in the various centers [9][10][11][18][19][20][21][22] . These centres are spread across the FCT and five geopolitical zones but excluding the north east geopolitical zone.…”
Section: Prevalencementioning
confidence: 99%
“…Out of the fifteen studies on children, fourteen spread across all geopolitical zones reported peak ages of 5-10 years (10,11,(13)(14)(15)(16)19,22,23,25,27,30,(39)(40)(41) . Only one study on children, from Sagamu reported a peak age of 1-5 years (18).…”
Section: Age Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, other studies demonstrated that neuroblastoma constituted 5.3%, 5.1%, 4.8%, 3.34% and 1.9% in Lagos, Kano, Uyo, Zaria and Enugu respectively. [4][5][6][7][8] Osteosarcoma is the eighth common cancer of childhood and its incidence is 4 cases in a million of children younger than 14 years. [26] Osteogenic sarcoma contributed (3 cases)11.11% of all childhood tumors in this study with a mean age of 8.67±1.15 years, peak age in the 6-10 years age groups and age range of 7 to 10 years.…”
Section: Resultsmentioning
confidence: 99%